2020
DOI: 10.1038/s41598-020-64227-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term fertilization alters soil properties and fungal community composition in fluvo-aquic soil of the North China Plain

Abstract: Different fertilization regimes can substantially influence soil fungal community composition, yet fewer studies try to control for the effects of nitrogen input. Here, we investigated the impact of fertilization with equal nitrogen upon soil properties and soil fungal diversity and community composition in the North China Plain in a long-term field experiment. Long-term (32 years) fertilization regimes were applied with equal amounts of nitrogen: no chemical fertilizer or organic manure; chemical fertilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 59 publications
2
25
0
1
Order By: Relevance
“…The reason may be the fertilization during the cultivation. Previous studies showed the fertilization can increase the richness of rhizospheric fungi [30][31][32]. Moreover, the sample Y4 had the highest Chao1 and ACE indices, indicating the maximal fungal species richness, which was consistent with the results in the Venn diagram (Figure 3b) and the clustering and NMDS (Figures 2 and 4) analysis: the rhizospheric soil with 4 years of cultivation had the most unique OTUs and its fungal community composition was different from the other samples.…”
Section: Relationship Between the Rhizospheric Fungal Community And T...supporting
confidence: 89%
“…The reason may be the fertilization during the cultivation. Previous studies showed the fertilization can increase the richness of rhizospheric fungi [30][31][32]. Moreover, the sample Y4 had the highest Chao1 and ACE indices, indicating the maximal fungal species richness, which was consistent with the results in the Venn diagram (Figure 3b) and the clustering and NMDS (Figures 2 and 4) analysis: the rhizospheric soil with 4 years of cultivation had the most unique OTUs and its fungal community composition was different from the other samples.…”
Section: Relationship Between the Rhizospheric Fungal Community And T...supporting
confidence: 89%
“…4a). Yao et al (2017) reported that changes in soil fungal community composition were closely related to soil nutrients in terms of enhancing the release of soil nutrients such as available N, P and K. In contrast, green manure provided several nutrients when it was incorporated into the soil, which enhanced fungal growth and led to noticeable improvements in soil fungal diversity (Wen et al 2020). Thus, incorporation of green manure into soil stimulated nutrient flux and increased fungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the majority of researches in this area have focused on the influences of organic and chemical fertilization on fungi (Ullah et al, 2019;Xiang et al, 2020). Applied organic fertilization generally has positive effect on fungal communities, such as increase of soil fungal diversity and decrease of the abundance of soil-borne fungal pathogens (Sun et al, 2016;Wen et al, 2020). Conversely, it was reported that the richness and abundance of soil fungi would be reduced, and the growth of potentially pathogenic fungi would be promoted following long-term addition of chemical fertilizers (Wang et al, 2018;Ye et al, 2020).…”
Section: Introductionmentioning
confidence: 99%